2020
DOI: 10.1001/jamadermatol.2019.4608
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Netherton Syndrome With Dupilumab

Abstract: describe was stung by the P noctiluca species. Furthermore, to our knowledge, the RCM characteristics of jellyfish sting have not been described to date. In this patient, RCM proved useful to identify the presence of nematocysts in the epidermis, confirming the clinical diagnosis of jellyfish sting and the related persistence of symptoms. Remarkably, in the follow-up visit after topical therapy, the dermoscopic and RCM features appeared dramatically reduced or no longer visible, paralleling the resolution of s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
39
1
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(44 citation statements)
references
References 5 publications
2
39
1
2
Order By: Relevance
“…Dupilumab is a human IgG4 monoclonal antibody that has resulted in positive outcomes in the treatment of AD. It suppresses the effect of cytokines IL‐4 and IL‐13 via targeting of the IL‐4 receptor alpha chain 4 . Increased production of IL‐4, IL‐5, IL‐13, and TNF‐alpha by Th2 pro‐allergen cells, which are promoted by the KLK5‐PAR‐2‐TSLP cascade in NS, might explain the efficacy of dupilumab in patients with NS 2 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Dupilumab is a human IgG4 monoclonal antibody that has resulted in positive outcomes in the treatment of AD. It suppresses the effect of cytokines IL‐4 and IL‐13 via targeting of the IL‐4 receptor alpha chain 4 . Increased production of IL‐4, IL‐5, IL‐13, and TNF‐alpha by Th2 pro‐allergen cells, which are promoted by the KLK5‐PAR‐2‐TSLP cascade in NS, might explain the efficacy of dupilumab in patients with NS 2 .…”
Section: Discussionmentioning
confidence: 99%
“…In both these cases, dupilumab led to sustained improvement, unlike the temporary response observed in our patient (Table 1). 4,5 …”
Section: Discussionmentioning
confidence: 99%
“…Our case report supports that IL‐4 receptor antagonism may dramatically reduce cutaneous inflammation in NS 1 . However, the levels of IL‐13, a prominent Th2 cytokine, in skin and blood were similar in patients with NS and healthy controls in recent studies 2,3 .…”
Section: Figurementioning
confidence: 92%
“…The lesser epidermal permeation in comparison with tacrolimus may offer an added advantage in patients with NS (Oji et al, 2005; Saif & Al‐Khenaizan, 2007). Biologics targeting IL4/IL13 (Dupilumab) (Steuer & Cohen, 2020), IL23 (Ustekinumab) (Volc et al, 2020), IL17 (Secukinuma, Ixekimab) (Claire et al, 2020; Luchsinger et al, 2020), and TNF‐α (Infliximab) (Fontao et al, 2020) have been reported as effective in some patients with NS. Treatment with IVIG was beneficial in seven patients with NS to date, although its immunomodulatory mechanisms are not understood (Renner et al, 2009; Small & Cordoro, 2016).…”
Section: Discussionmentioning
confidence: 99%